Effects of different treatment methods on clinical efficacy and fertility outcomes of patients with adenomyosis - Zhaoping Chu; Ligang Jia; Jun Dai; Qi Wu; Fei Tian; Suning Bai (BMC, 2024)
Abstract Objective This trial was to investigate the effect of different treatment methods on the clinical efficacy and fertility outcome of patients with adenomyosis. Methods In total, 140 patients with adenomyosis were evenly and randomly allocated into group A (laparoscopic surgery), group B (laparoscopic surgery combined with gonadotropin-releasing hormone analogs [GnRH-a]), group C (ultrasound-guided percutaneous radiofrequency ablation), and group D (ultrasound-guided percutaneous radiofrequency ablation combined with GnRH-a). On the 3rd day after surgery, patients in group B and group D were subcutaneously injected with GnRH-a (Leuprorelin Acetate SR for Injection) at 3.75 mg/time, once every 4 weeks, for a total of 3 months. The therapeutic effects of the 4 groups were compared, including menstrual volume, dysmenorrhea score, uterine volume, clinical efficacy, luteinizing hormone (LH), estradiol (E2), and follicle-stimulating hormone (FSH) levels, CA125 levels, recurrence, pregnancy status, and pregnancy outcomes. Results After treatment, the menstrual volume of 4 groups was lowered, dysmenorrhea, Visual Analog Scale (VAS) score, LH, FSH, E2, and CA125 levels were reduced, and uterine volume was decreased. The menstrual volume, VAS score, levels of LH, FSH, E2, and CA125, and uterine volume were reduced in groups B, C, and D compared with group A, and the decrease was more significant in group D. The total effective rate of group D was 100.00%, which was higher than that of group A (71.43%), group B (80.00%), and group C (82.86%). After one year of drug withdrawal, the recurrence of hypermenorrhea, dysmenorrhea, uterine enlargement, and excessive CA125 in group D was significantly lower than that in groups A, B and C, and the recurrence in groups B and C was significantly lower than that in group A (P < 0.05). Compared with groups A, B, and C, group D had a higher pregnancy rate, natural pregnancy rate, and lower in vitro fertilization-embryo transfer rate (P < 0.05), but showed no significant difference in pregnancy outcomes. Conclusion Ultrasound-guided percutaneous radiofrequency ablation combined with Leuprorelin Acetate is effective in the treatment of adenomyosis, which can effectively relieve clinical symptoms, protect postoperative ovarian function, reduce recurrence rate, alleviate pain, and improve quality of life.